TRANSPARANSI PEMERINTAH DESA TERHADAP PENGELOLAAN BANTUAN LANGSUNG TUNAI DI DESA MARIO KECAMATAN KULO KABUPATEN SIDENRENG RAPPANG - Ameliah, Nurul; Jabbar, Abdul; Nonci, Nurjannah (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This research aims to determine the transparency of the village government and the management of direct cash assistance in Mario Village, as well as the influence of village government transparency on the management of direct cash assistance in Mario Village, Kulo District, Sidenreng Rappang Regency. The independent variable used is village government transparency and the dependent variable used is the management of direct cash assistance. The sampling technique in this research is based on a saturated sampling technique or the entire population is used as a sample because the population is less than 100, namely 58 recipients of direct cash assistance. This type of research is quantitative descriptive. The data collection techniques used were observation, literature study, and questionnaires. The data analysis technique uses descriptive statistical analysis, validity test, reliability test, and simple linear regression analysis which is processed using the SPSS type 21 application. The results of this research show that village government transparency (X) was obtained with a percentage of 66%, indicating that transparency is quite good, indicating that there is a significant effort from the village government to strive for clear and easy transparency. However, further evaluation is still needed on what factors can increase transparency. For the management of direct cash assistance (Y), the resulting percentage of 71% is quite good, although there is still room to reach a higher level with further evaluation to help identify areas that need improvement. In addition, the significance value of tcount is greater than ttable (3,458 > 1,671), so it can be concluded that Ha is accepted and Ho is rejected, so that village government transparency has a positive and significant effect on the management of direct cash assistance in Mario Village, Kulo District, Sidenreng Rappang Regency